Influence of Nickel on the Microstructure, Mechanical Properties, and Corrosion Resistance of Laser-Welded Super-Duplex Stainless Steel - Cruz Junior, E. J. da; Gallego, J. [UNESP]; Settimi, A. G.; Gennari, C.; Zambon, A.; Ventrella, V. A. [UNESP] (Springer, 2021)
Super-duplex stainless steel (SDSS) exhibits an austenite-ferrite dual-phase structure, which promotes many benefits upon single-phase grades, such as high mechanical strength and corrosion resistance. Welding process results in an unbalanced microstructure, with large amount of ferrite, which compromise SDSS's properties. This paper investigates the effect of using electrolytic nickel foils as an addition metal on UNS S32750 SDSS Nd:YAG pulsed laser welding, through the evaluation of the microstructure, hardness, tensile strength, and corrosion resistance of the weld bead. Six conditions were investigated: autogenous welding and with addition of nickel, varying the thickness of nickel foil added. Microstructural analysis reveals an increase in volume fraction of austenite for the conditions with addition of nickel. Using a 30 mu m thick nickel foil, approximately equal amount of austenite and ferrite was obtained in the weld bead. The higher microhardness was obtained for the autogenous welding, 400 HV and decreased with the addition of nickel. The tensile strength decreased 4% in the experimental conditions with high nickel addition. The corrosion resistances were the same for all the conditions with addition on nickel, regardless of the nickel foil thickness added, but it compared to autogenous welding the CPT's increased approximately 14 degrees C.
Keywords: corrosion resistance; mechanical properties; microstructure; Nd; YAG pulsed laser welding; nickel addition; super-duplex stainless steel